2017
DOI: 10.1002/ejic.201700635
|View full text |Cite
|
Sign up to set email alerts
|

Facile Reversible Benzophenone Insertion into Rare‐Earth Metal Pyrazolate Complexes

Abstract: Treatment of the homoleptic Ce IV pyrazolate complex [Ce(Me 2 pz) 4 ] 2 (Me 2 pz = 3,5-dimethylpyrazolato) with benzophenone (bp) led to the formation of an Me 2 pz-substituted diphenylmethoxy-(N,O)-chelating ligand (pdpm), possibly metal-templated through initial coordination of bp to the cerium atom and subsequent bp insertion into the Ce-N(Me 2 pz) bond. This coordination/insertion process was shown to be reversible, leading to a complex sequence of equilibria involving multiple degrees of insertion/de-inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…In a previous study we found that the reaction between 1 and benzophenone affords Me 2 pz‐functionalized diphenylmethoxy ligand moieties via a cascade of benzophenone association/dissociation and nucleophilic attack by the Me 2 pz co‐ligands, which is facilitated by weakening of the ketone C=O double bond upon coordination to cerium(IV) . The present ligand transformation may bear some similarity, being triggered by the nucleophilic attack of the “activated” Si−H functionality by a pyrazolato ligand.…”
Section: Resultsmentioning
confidence: 69%
“…In a previous study we found that the reaction between 1 and benzophenone affords Me 2 pz‐functionalized diphenylmethoxy ligand moieties via a cascade of benzophenone association/dissociation and nucleophilic attack by the Me 2 pz co‐ligands, which is facilitated by weakening of the ketone C=O double bond upon coordination to cerium(IV) . The present ligand transformation may bear some similarity, being triggered by the nucleophilic attack of the “activated” Si−H functionality by a pyrazolato ligand.…”
Section: Resultsmentioning
confidence: 69%
“…As a consequence of the equilibrium between potential alternative oligomers formed in the presence of only one equivalent of CO 2 per cerium, the interpretation of the ambient‐temperature NMR spectrum was difficult. This was already experienced for the insertion of benzophenone into the Ce−N(Me 2 pz) bond . Upon heating to 90 °C, CO 2 was liberated and [Ce(Me 2 pz) 4 ] re‐formed (see Figure S14).…”
Section: Resultsmentioning
confidence: 92%
“…The Ce À N and Ce À O bond lengths average 2.528 and 2.255 , respectively, thus matching the values found in the benzophenoneinserted product [Ce(Me 2 pz) 2 (pdpm) 2 ] (Ce1ÀN1 2.564 , Ce1ÀO1 2.173 ; pdpm = (3,5-dimethylpyrazol-1-yl)diphenylmethanolate). [23] Other homoleptic Ce IV complexes, [Ce-(L) 4 ] (with L as a donor-functionalized alkoxy ligand engaged in a 5-membered chelate to cerium), also have similar Ce À O bond lengths as those in 2, thus highlighting a common chelating coordination motif. [24,25] Seemingly, no delocalization occurs across the O=CÀO fragment, which exhibits average CÀO bond lengths of 1.207 (terminal) and 1.291 (bridging).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations